Training Life-Cycle Psychoanalysts: Integrated Psychoanalytic Education. Issue 1 (31st December 2022) - Novick, Jack; Novick, Kerry Kelly
ABSTRACT: The authors summarize the evolution of child psychoanalysis, including Freud's extensive pediatric experience, to introduce Anna Freud's aspiration for an integrated psychoanalysis, comprising the whole life cycle. The authors suggest that her disappointment that child analysis did not receive wider acceptance in the field is related to the phenomenon of "childism, " a pervasive prejudice against children. Nevertheless, some progress in organizing integrated child and adult psychoanalytic trainings has been made; the Michigan Model of Integrated Training is an example and its relation to the IPA's adoption of an available Integrated Training Track is described. Resistances, problems and erosions are also discussed. At the time of writing, the authors suggest that, while many forces are arrayed which undermine integration of trainings, enthusiastic and sustained effort may create a viable future for integrated psychoanalytic education.